ANALISIS PEMBELAJARAN IPS DI SD/MI DALAM KURIKULUM 2013 - Azizah, Amirah Al May (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
Problematic, that appears in the learning process on the previous curriculum is centered on the teacher (teacher center), with the result that there is no improvisation that causes learners to glued only on the basic materials. In the new curriculum (2013) the learning process began to focus on the learners (student center). This is outlined in the discussion with the analysis of ips learning in elementary school/madrasah ibtidaiah 2013 curriculum. Began from the changes of a new curriculum, which is integratif theme, it is expected the students to be able to be an active individual, creative, critical thinking, have teamwork and could fight in the competition of global. The paper uses library research methods. Collecting data in this study conducted by reviewing a few relevant sources such as books, articles or journal, and other documents. Data analysis technique uses content analysis. Â The results of research proved that IPS learning in elementary school/madrasah ibtidaiah in the 2013 curriculum is an collection from various aspects, which contains the scientific structure of IPS in elementary school/madrasah ibtidaiah, the development characteristics of students, high-level thinking ability or HOTS (higher orders thinking), financial literacy, literacy in culture and citizenship, digital literacy, and character education